Non-acid reflux and sleep apnea: the importance of drug induced sleep endoscopy - Carlos O’Connor-Reina; Jose Maria Ignacio Garcia; Peter Baptista; Maria Teresa Garcia-Iriarte; Carlos Casado Alba; Monica Perona; Paz Francisca Borrmann; Laura Rodriguez Alcala; Guillermo Plaza (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background We present the first case of a patient with obstructive sleep apnea syndrome (OSA), where drug induced sleep endoscopy was helpful to suspect a non-acid reflux disease and showed an improvement in a swollen epiglottis after treatment. Patient ameliorated significantly his disease only with medical therapy. Case presentation A 54-year-old man without significant anatomical findings with obstructive sleep apnea syndrome and non-acid gastroesophageal reflux disease (GERD) disease whose Apnea- hypopnea index (AHI) was significantly reduced with the intake of 500 mg of sodium alginate twice a day for 6 months. Conventional digestive tests such as esophagoscopy and simple- and double-channel 24-h pH-metry suggested mild GERD. Conventional proton-pump inhibitor treatment with pantoprazole (40 mg daily) was started without any improvement in his sleep. Multichannel intraluminal 24-h impedanciometry indicated the presence of severe pathological GER of gaseous origin. The patient’s AHI decreased from 25.3 at baseline to 8 after treatment with sodium alginate. A drug-induced sleep endoscopy study showed the changes before and after this treatment and was helpful for the diagnosis. Conclusions Thus, medical treatment can be a therapeutic option in some patients with OSA. Multichannel 24-h impedanciometry should be performed when nonacid GERD is suspected.